THE SOCIAL COMPETENCE CONCEPT DEVELOPMENT IN HIGHER EDUCATION - Genute Gedviliene; Silvija Gerviene; Ausrine Pasvenskiene; Simona Ziziene (European Scientific Journal, ESJ, 2014)
The article seeks to develop the concept of social competence in higher education based not only on theoretical background but also on the reflections of social competence in European Union (EU) and national (in this case – Lithuanian) regulations of higher education. Theoretical analysis revealed that social competence as a concept has many definitions. As a result it was recognized that the set of skills defining social competence differs depending on the context where they are exploredand the particular components of the social competence in education are revealed. They served as the base to identify how social competence reveals itself in higher education. In order to carry out this task the empirical research – relevant document analysis was performed.